Severity of dehiscences and fenestrations in ortho-surgical patients with Class III malocclusion evaluated with cone beam computed tomography - Vásquez Cabrejos, Carol del Pilar (2020)
Objective. Determine the frequency and severity of vestibular dehiscences and fenestrations of anterior teeth in orthodontic–surgical patients with skeletal malocclusion, Angle’s Class III; evaluated with presurgical cone-beam computed tomography Methods. Thirty cone-beam computed tomographies of skeletal malocclusion Class III patients with presurgical orthodontic treatment; were evaluated. The sample consisted of on – probabilistic and consecutive cases seen at the Universidad Nacional Mayor de San Marcos Dental School and at the Guillermo Almenara Irigoyen National Hospital’s Dental Service in Lima, Perú in 2018. The dehiscence was considered as the apical migration of the alveolar margin bone starting at 2 mm from the cementoenamel junction, and the fenestration was considered as the exposure of the root portion, excluding the alveolar margin bone; starting at 0.5 mm. Results. Out of all tomographies, 43.3% were from women and 56.7% were from men. Dehiscences were observed in all tomographies, most frequently in the mandible (91.6%) and inferior canines (100%). Fenestrations were observed in 66.7%, most frequently in the maxilla (28.3%) and maxillary canines (31.7%). The severe level was more frequently in dehiscences (65.8%) and fenestrations (13.9%), affecting the inferior canines (100%) and maxillary canines (26.7%), respectively in each defect. Conclusions. Dehiscences were observed in all tomographies, affecting most frequently mandible canines in severe level and fenestrations were observed in most tomographies, affecting most frequently maxillary canines in severe level.